The write way to spell: printing vs. typing effects on orthographic learning - Ouellette, Gene; Tims, Talisa (Frontiers in Psychology, 2014)
Prior research has shown superior orthographic learning resulting from spelling practice relative to repeated reading. One mechanism proposed to underlie this advantage of spelling in establishing detailed orthographic representations in memory is the motoric component of the manual movements evoked in printing or writing. This study investigated this contention directly by testing the effects of typing versus printing on the orthographic learning achieved through spelling practice, and further evaluated whether practice modality interacts with pre-existing individual characteristics. 40 students in grade 2 (mean age 7 years 5 months) were introduced to 10 novel non-words. Some of the students practiced spelling the items by printing, while the others practiced spelling them on a keyboard. Participants were tested for recognition and spelling of these items 1 and 7 days later. Results revealed high rates of orthographic learning with no main effects of practice modality, testing time, or post-test modality. Hierarchical regression analyses revealed an interaction between typing proficiency and practice modality, such that pre-existing keyboarding skills constrained or facilitated learning within the typing-practice group. A similar interaction was not found between printing skills and learning within the printing group. Results are discussed with reference to both prominent reading theory and educational applications. Provisional manuscript of the registered report available here Full manuscript expected summer 2014.